The nature and propagation of shocks in the euro area: a comparative SVAR analysis. (2017) - Coco, Alberto; Silvestrini, Andrea
This paper investigates the nature and the propagation of macroeconomic shocks hitting the euro area, in order to draw indications on the functioning and viability of the monetary union after 15 years from its inception. Structural VAR models identified with sign restrictions for a large set of euro-area countries allow comparing the properties of three independent shocks over different sample periods, before and after the start of the EMU. Results show that, up to the third quarter of 2008, shocks on average have increased their co-movement and decreased their size and persistence in eurozone countries, compared with two control countries inside the European Union but outside the euro area (UK and Sweden). Conversely, following the outbreak of the global financial crisis, shocks have become on average more harmful for the euro area, as testified by their larger size and persistence relative to those in the two control countries.